Feed and Disease at Olive Flounder (Paralichthys olivaceus) Farms in Korea - Joo-Young Jung; Soohwan Kim; Kyochan Kim; Bong-Joo Lee; Kang-Woong Kim; Hyon-Sob Han (Fishes, 2020)
The objective of this study was to conduct field experiments comparing formulated (extruded pellets (E.P)) and raw-fish (moist pellets (M.P)) feeds at two flounder aquaculture farms for six months to obtain the basic data necessary for improving aquafarmers’ awareness of feed-quality issues and firmly establish and expand the use of formulated feed. According to the results, the M.P group was higher in weight gain, feed efficiency ratio, protein efficiency ratio, and specific growth rate and lower in mortality rate than the E.P group. All cases of mortality were caused by six kinds of disease, four of which (Vibrio sp., Edwardsiella sp., Streptococcus sp., and Scuticociliates) were common to the two groups, whereas Lymphocystis arose only in the M.P group and abdominal inflation only in the E.P group at both farms. As for mortality in the present experiment, the numbers were 1047 at Da-Hae farm and 1167 at Global farm, with more fish dying in the E.P tanks than in the M.P tanks. By multiplying the number of deaths by selling price, the economic losses were $9650 and $10,756, respectively. Therefore, it should be considered an urgent priority to develop flounder-exclusive formulated feed for improved digestion and absorption rate and also to establish a water-quality-improvement management plan.